A Computational Framework for Studying Gut-Brain Axis in Autism Spectrum Disorder - Mohammad, Faiz Khan; Palukuri, Meghana Venkata; Shivakumar, Shruti; Rengaswamy, Raghunathan; Sahoo, Swagatika (Frontiers in Physiology, 2022)
Introduction The integrity of the intestinal epithelia is crucial for human health and is harmed in autism spectrum disorder (ASD). An aberrant gut microbial composition, resulting in gut-derived metabolic toxins would damage the intestinal epithelium jeopardizing tissue integrity. These further reach the brain via the gut-brain axis, disrupting brain's normal functioning. A mechanistic understanding of metabolic disturbances in the brain and gut is essential to design effective therapeutics and early intervention to block disease progression. Herein, we present a novel computational framework that integrates constraint-based tissue-specific metabolic (CBM) and whole-body physiological pharmacokinetic (PBPK) modeling for ASD. Further, the role of gut microbiota, diet, and oxidative stress is analyzed within ASD context. Methods A representative gut model capturing host-bacteria and bacteria-bacteria interaction was developed using CBM techniques and patient data. Simultaneously, PBPK model of toxin metabolism was assembled incorporating multi-scale metabolic information. Further, dynamic flux balance analysis was applied to integrate CBM and PBPK. Effectiveness of probiotic and dietary intervention to improve autistic symptoms was tested on the integrated model. Results The model accurately highlighted the critical metabolic pathways of the gut and brain that are known to be associated with ASD. These includes central carbon, nucleotide, and vitamin metabolisms in the host gut, whereas, mitochondrial energy, and amino acid metabolisms in the brain. The proposed dietary intervention revealed that a high fibre diet is more effective than a western diet in reducing toxins produced inside the gut. The addition of probiotic bacteria Lactobacillus acidophilus, Bifidobacterium longum longum, Akkermansia muciniphila, and Prevotella ruminicola to the diet restores gut microbiota balance, thereby lowering oxidative stress in the gut and brain. Conclusions The proposed computational framework is novel in its applicability, as demonstrated by determining the whole-body distribution of ROS toxins and metabolic association in ASD. In addition, it emphasized the potential for developing novel therapeutic strategies to alleviate autism symptoms. Notably, the presented integrated model validates the importance of combining PBPK modelling with COBRA-specific tissue details for understanding disease pathogenesis.